Celluloid symphonies : texts and contexts in film music history - Hubbert, Julia Bess (University of California Press, 2011)
"Celluloid Symphonies is a unique sourcebook of writings on music for film, bringing together fifty-three critical documents, many previously inaccessible. It includes essays by those who created the music--Max Steiner, Erich Korngold, Jerry Goldsmith, Elmer Bernstein, and Howard Shore--and outlines the major trends, aesthetic choices, technological innovations, and commercial pressures that have shaped the relationship between music and film from 1896 to the present."--From publisher's description.